The Role Of Digital Transformation In Improving Innovation Management Mechanisms In School Educational Institutions (Eurasian Research Bulletin, 2026)
This article theoretically analyzes the role of digital transformation in improving innovative management mechanisms in preschool educational institutions. The study studies the content and interrelationship of the concepts of "digital transformation", "innovative management" and "digital competence". The theoretical foundations of automating administrative processes in the preschool education system, using information-based systems in decision-making, and ensuring effective communication with parents are identified. Various scientific approaches - systemic theory, theory of diffusion of innovations, TPAK model and the concept of digital competence - are compared and analyzed. As a result, four main functional areas of digital transformation in the management of preschool educational institutions are formed: administrative, economic, socio-communicative and information-analytical. Also, obstacles to the implementation of digital transformation and ways to overcome them are identified. The theoretical results achieved in the article made it possible to identify new areas of scientific research on the modernization of preschool education management